A False Spider Mite, Brevipalpus californicus (Banks) (Archnida: Acari: Tenuipalpidae) - Harold A. Denmark (EDIS, 2006)
EENY-384, a 4-page illustrated fact sheet by H. A. Denmark, is included in the Featured Creatures series. It describes this mite pest with an extensive host range, its synonymy, distribution, description, hosts, economic importance, management, survey and detection, management, and selected references. Published by the UF Department of Entomology and Nematology, July 2006.